Desain Konsep Pengembangan Wisata Halal Menara Kudus Dengan Konsep Gusjigang - Munzaroah, Shela Dwi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to determine the development of halal tourism in Kudus Regency and to determine the development of the Kudus Tower with the Gusjigang concept. This research is a qualitative research using descriptive method, the data used are primary data and secondary data, with data collection, interviews, observation, and documentation. The results of this study can be concluded that halal tourism is a place of recreation to let go of busyness that does not deviate from the teachings of Islamic law. In the development of the Kudus Tower tourism, it has become a tourist spot that is visited by many tourists in various cities in Indonesia, becoming an attraction and interest among the public with the beauty of its buildings. The Menara Kudus Mosque is one of the witnesses to the development of the Islamic religion brought by Sunan Kudus. The concept of Gusjigang is a philosophy that is embedded in the personality of the saint. The Gusjigang philosophy is one that has noble values and was taught by the ancestors of Sunan Kudus. For this reason, the Kudus community needs to instill the values of religious education to pass on to the next generation which can be used as a guide by the community.